Ca-ATPase Activity and Protein Composition of Sarcoplasmic Reticulum Membranes Isolated from Skeletal Muscles of Typical Hibernator, the Ground Squirrel Spermophilus undulatus. Issue 6 (December 2001) - Malysheva, Anna N.; Storey, Kenneth B.; Lopina, Olga D.; Rubstov, Alexander M.
Abstract : Ca-ATPase activity in sarcoplasmic reticulum (SR) membranes isolated from skeletal muscles of the typical hibernator, the ground squirrel Spermophilus undulatus, is about 2-fold lower than that in SR membranes of rats and rabbits and is further decreased 2-fold during hibernation. The use of carbocyanine anionic dye Stains-All has revealed that Ca-binding proteins of SR membranes, histidine-rich Ca-binding protein and sarcalumenin, in ground squirrel, rat, and rabbit SR have different electrophoretic mobility corresponding to apparent molecular masses 165, 155, and 170 kDa and 130, 145, and 160 kDa, respectively; the electrophoretic mobility of calsequestrin (63 kDa) is the same in all preparations. The content of these Ca-binding proteins in SR membranes of the ground squirrels is decreased 3–4 fold and the content of 55, 30, and 22 kDa proteins is significantly increased during hibernation.